The K[+] channel gene ether a go-go is required for the transduction of a subset of odorants in adult Drosophila melanogaster. - Dubin, A.E.; Liles, M.M.; Harris, G.L. (Journal of Neuroscience, 1998)
The functional identity of an olfactory receptor neuron is determined in part by its repertoire of responses to odorants. As an approach toward understanding the contributions of particular conductances to olfactory neuron excitability and odor discrimination, we have investigated the role of the putative cyclic nucleotide-modulated K+ channel subunit encoded by the ether a go-go (eag) gene in odorant responsiveness in Drosophila melanogaster. Four independent mutant eag alleles exhibited reduced antennal sensitivity to a subset of nine odorants, all having short aliphatic side chains: ethyl butyrate (EB), propionic acid, 2-butanone, and ethyl acetate. Significantly fewer eag antennal neurons responded to EB compared with control neurons; the proportion sensitive to 2-heptanone was similar to controls. Two aspects of the character of EB-induced excitability were affected by mutations in eag. First, fewer EB-induced inhibitory responses were observed in eag mutants, and second, fewer excitatory odorant responses dependent on extracellular Ca2+ were observed. Furthermore, modulation of neuronal excitability by membrane-permeant cyclic nucleotide analogs was largely eag dependent. Focal application of high K+ saline to sensillae altered the excitability of the majority of neurons from wild-type but not eag antennae, suggesting that Eag may have a dendritic localization.